Manejo hortícola y su relación con el nivel de aplicación tecnológica de horticultores de la carretera Iquitos Nauta. Loreto, 2019 - Bardales de Barrera, Lidia del Carmen (2022)
The purpose of the research study was to obtain productive indicators in order to propose improvements in the horticultural management of the horticulturists of the 13 de febrero community, located on the Iquitos - Nauta highway. The question posed was: What is the relationship between horticultural management and the level of technological application of the horticulturists of the Iquitos - Nauta highway in the Loreto region, in 2019?. The general objective: To determine the relationship between horticultural management and the level of technological application of the horticulturists of the Iquitos - Nauta road. The type of study was cross-sectional - analytical, with quantitative approach, correlational level and non-experimental design; the sample consists of 55 horticultural producers. The instrument used was a questionnaire with validity of 80% and reliability 82%. Whose results were: 41.8% have a low level in the management of horticultural, 40.0% a medium level and 18.2% a high level in the management of horticultural. 52.7% have a low level of technological application, 29.1% a high level and 18.2% an average level of technological application in their planting and harvesting activities. To determine the correlation between horticultural management and level of technology application in horticulturists, and to verify the hypothesis, Spearman's Rho correlation coefficient was applied; obtaining a positive correlation coefficient of 0.758, with a value of significance p<0.05, that is to say the greater the valuation of horticultural management, the greater the use of the level of technology and vice versa. The results will contribute to promoting training programs on appropriate technologies, aimed at strengthening the knowledge and practices of the horticulturist, and thus generate greater productivity, yield and quality of vegetables in the region and country.